(untitled) (Research, Society and Development, 2025)
Objective: This study investigated the profile of drowning victims in the state of Santa Catarina - Brazil and the profile of deaths from the same cause, aiming to map areas with the highest incidence and guide preventive actions. Method: A cross-sectional quantitative methodology was used, analyzing secondary data from 39,247 rescues and 1,679 deaths between 2015 and 2023, obtained from the Santa Catarina Military Fire Department and the Mortality Information System. Results: The results indicated that 93.4% of rescues occurred in coastal cities, particularly Florianópolis, Balneário Camboriú, and Bombinhas. The most affected age group was 20 to 39 years old, with a predominance of male, white, and single victims. Although the number of rescues increased, there was a 21.56% reduction in the mortality rate over the period. Conclusion: The need to intensify preventive policies, especially targeting high-risk groups, such as young men, and to promote public awareness campaigns on water safety is highlighted. The effectiveness of rescue operations has been proven, but the increase in incidents reflects the persistence of risky behaviors, highlighting that prevention is essential to minimize drowning incidents and their socioeconomic impacts in the state.